On values in non-routine mathematical problems for senior high school students. (February 2019) - Indaryanti, I; Aisyah, N; Winarni, S; Astuti, P
Abstract: This study aims to describe values in non-routine problems for senior high school students. This research used the qualitative method. The subjects of this study were the senior high school students. The data collection techniques used interviews and observations. An interview was used to get information about curriculum and the abilities of the students. The observation was used to find out the mathematical values contained in the non-routine problems. The results of the study show that in non-routine problems there are values that exist in mathematical values. These values are rationalism, objectivity, control, progress, openness, and mystery.